The Effect Of Job Training, Work Motivation, And Career Development on Employee Performance at PT. Sinar Harapan Roof Kebun Tebeng Bengkulu City - Arda Pratiwi; Islamuddin Islamuddin (UNIVED Press, 2024)
This study aimed to determine the effect of job training, work motivation, and careerdevelopment on employees’ performance at PT. Sinar Harapan Roof Kebun Tebeng Bengkulu City. This study used quantitive method. The data collection techniques used observation, interview and quitionnaire. The population of this stufy were all employess of PT. Sinar Harapan Roof Kebun Tebeng In Bengkulu City with totaling 32 people by using the saturated sampling technique. The result of study show that multiple linear regression, the regression equation Y = 5.234 + 0.115 (x1) + 0.169 (X2) + 0.009 (X3) is obtained. This equatin can be explained by the positive effect of eavh independent variable, on employees’ performance (Y). as well as the coefficient of determination of R2= 0.675 or around (67.5%) through hypothesis testing together (simultaneously) and individually (partially) and by the F test and T test, job training (X1), work motivation (X2), and career development (X3) are 0.014. it means that the value of fsig<0.05 indicates that together and tahat has a significant effect.